Contribution to the knowledge of the fauna of Ichneumonidae (Hymenoptera: Ichneumonoidea) from Iran. - Ghahari, Hassan; Jussila, Reijo (Contributions to Entomology = Beiträge zur Entomologie, 2016)
In this paper, 17 species of the family Ichneumonidae (Hymenoptera) from 9 subfamilies, Anomaloninae, Cremastinae, Cryptinae, Ctenopelmatinae, Ichneumoninae, Orthocentrinae, Pimplinae, Tersilochinae and Tryphoninae, are listed from different regions of Iran. Three species, Gelis anthracinus (Förster, 1850), Eusterinx (Dallatorrea) circaea Rossem, 1982 and Barycnemis agilis (Holmgren, 1860), are new records for the fauna of Iran.KeywordsHymenoptera, Ichneumonidae, faunistic list, new records, Iran.